1998
DOI: 10.1083/jcb.141.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Biogenesis: Involvement of ARF and Coatomer

Abstract: Peroxisomal membrane protein (Pmp)26p (RnPex11p), a major constituent of induced rat liver peroxisomal membrane, was found to contain a COOH-terminal, cytoplasmically exposed consensus dilysine motif with the potential to bind coatomer. Biochemical as well as immunocytochemical evidence is presented showing that peroxisomes incubated with preparations of bovine brain or rat liver cytosol recruit ADP-ribosylation factor (ARF) and coatomer in a strictly guanosine 5′-O-(3-thiotriphosphate)–dependent manner. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
131
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 70 publications
9
131
0
1
Order By: Relevance
“…That BFA interferes with the formation of coated vesicles at ER and Golgi membranes (Nebenfü hr et al, 2002) suggests the involvement of vesicle transport in peroxisomal sorting and/or biogenesis. In support of this hypothesis, the AAA-ATPases Pex1p and Pex6p from Pichia pastoris were localized in cell fractionation experiments to vesicles that were distinct from peroxisomes (Faber et al, 1998), and Just and coworkers demonstrated that rat liver Pex11p may promote vesiculation of peroxisomes by recruiting ADP-ribosylation factor and coatomer (Passreiter et al, 1998;Anton et al, 2000). Although similar experimental data are not yet available for plant proteins, a set of 15 Arabidopsis Pex orthologs, including Pex1p, Pex3p, Pex6p, and Pex11p, have been identified through recent comparisons of human, mouse, and yeast Pex sequences with Arabidopsis sequences (Baker et al, 2000;Mullen et al, 2001a;Charlton and Ló pez-Huertas, 2002).…”
mentioning
confidence: 79%
“…That BFA interferes with the formation of coated vesicles at ER and Golgi membranes (Nebenfü hr et al, 2002) suggests the involvement of vesicle transport in peroxisomal sorting and/or biogenesis. In support of this hypothesis, the AAA-ATPases Pex1p and Pex6p from Pichia pastoris were localized in cell fractionation experiments to vesicles that were distinct from peroxisomes (Faber et al, 1998), and Just and coworkers demonstrated that rat liver Pex11p may promote vesiculation of peroxisomes by recruiting ADP-ribosylation factor and coatomer (Passreiter et al, 1998;Anton et al, 2000). Although similar experimental data are not yet available for plant proteins, a set of 15 Arabidopsis Pex orthologs, including Pex1p, Pex3p, Pex6p, and Pex11p, have been identified through recent comparisons of human, mouse, and yeast Pex sequences with Arabidopsis sequences (Baker et al, 2000;Mullen et al, 2001a;Charlton and Ló pez-Huertas, 2002).…”
mentioning
confidence: 79%
“…Moreover, the ADP-ribosylation factor and coatomers known to be important in membrane vesicle formation also seem to be involved in peroxisome biogenesis (30). The functions of these factors were discussed in terms of both vesicle formation from the endoplasmic reticulum and the fission of preexisting peroxisomes (30). Thus, it is again a current question as to whether peroxisomes are formed from preexisting peroxisomes or endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…In a yeast species, the proteins involved in the secretory pathways and peroxisome assembly seem to be functionally overlapping (29). Moreover, the ADP-ribosylation factor and coatomers known to be important in membrane vesicle formation also seem to be involved in peroxisome biogenesis (30). The functions of these factors were discussed in terms of both vesicle formation from the endoplasmic reticulum and the fission of preexisting peroxisomes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Of the many PEX 1 genes and products (peroxins) required for peroxisome biogenesis, only PEX11 has been shown to have a conserved role in peroxisome division (7)(8)(9)(10)(11)(12)(13). The overexpression of PEX11 promotes peroxisome elongation and subsequent division, whereas loss of PEX11 results in reduced peroxisome abundance (7,8,12,14).…”
mentioning
confidence: 99%